Comparison of Ranibizumab monotherapy versus combination of Ranibizumab with photodynamic therapy with neovascular age‐related macular degeneration. (14th December 2012) - Krebs, Ilse; Vécsei Marlovits, Veronika; Bodenstorfer, Johannes; Glittenberg, Carl; Ansari Shahrezaei, Siamak; Ristl, Robin; Binder, Susanne
Abstract. Purpose: Modern therapy of neovascular age‐related macular degeneration consists in intravitreal injections of inhibitors of the vascular endothelial growth factor. An increasing number of these injections is required not only in monthly but also in as‐needed treatment regimen. In this study, it should be examined whether an additional administered photodynamic therapy (PDT) can considerably reduce the number of injection. Methods: In this prospective, randomized study carried out in three large hospitals of Vienna eyes with neovascular age‐related macula degeneration were included. Patients were randomized to either Ranibizumab monotherapy or combined standard fluence PDT and Ranibizumab therapy. All patients received a loading dose of three intravitreal Ranibizumab injections and were thereafter treated in an as‐needed regimen based on distance acuity and retinal thickness values. In the combined treatment group, PDT was administered 1 day after the first Ranibizumab injection. Results: Fifty‐one patients were randomized, 44 were finally included (four screening failures and three withdrawals). Twenty‐four patients were assigned to the monotherapy and 20 patients to the combined treatment group. Fewer injections were required in the combined treatment group (4.7 versus 6.3). Overall the patients lost 0.5 letters; in the combined treatment group, the patients lost mean 7.1 letters; in the monotherapy group, they gained mean 5.1 letters. Retinal thickness decreased significantly in both groups. Conclusion: A significant reduction of the number of required intravitreal injections could be achieved by the additional PDT treatment, but was accompanied by a worse functional outcome in this group.